Identification value of dog (Canis lupus familiaris) and cat (Felis catus) hair based on selected features of morphology in the context of forensic examinations - Karczmarczyk, Sebastian; Gryzińska, Magdalena (Issues of Forensic Science, 2019)
Theoretical assumptions of this the work present the range of selected morphological features of the dog (Canis lupus familiaris) and cat (Felis catus) hair. The practical part consisted in morphological analysis of 270 samples of dog and cat hair recovered during an investigation conducted in the territory of Cracow by the local Prosecutor’s Office. For this purpose, microscopic slides were made and analysed under an optical microscope for: colour, life cycle phase, shape of the medulla and the end of hair. Analysis of the results from the part dedicated to the examination allows answering the question whether microscopic analysis of dog and cat hairs based on selected morphological features allows identification of species. Teoretyczne założenia tematu pracy przedstawiają zakres wybranych cech morfologicznych sierści psa (Canis lupus familiaris) i kota (Felis catus). W ramach części praktycznej dokonano analizy morfologicznej 270 próbek sierści psa i kota zabezpieczonych podczas śledztwa prowadzonego na terytorium Krakowa przez miejscową prokuraturę. W tym celu sporządzono preparaty mikroskopowe i za pomocą mikroskopu optycznego analizowano je pod kątem: barwy, fazy cyklu życiowego, kształtu rdzenia oraz zakończenia. Analiza wyników z części badawczej pozwala odpowiedzieć na pytanie, czy analiza mikroskopowa sierści psa i kota oparta na wybranych cechach morfologicznych umożliwia jej identyfikację gatunkową.